Depression and state anxiety scores during assisted reproductive treatment are associated with outcome: a meta-analysis. Issue 6 (June 2018) - Purewal, Satvinder; Chapman, Sarah C.E.; van den Akker, Olga B.A.
Abstract: This meta-analysis investigated whether state anxiety and depression scores during assisted reproductive technology (ART) treatment and changes in state anxiety and depression scores between baseline and during ART treatment are associated with treatment outcome. PubMed, PsycInfo, Embase, ScienceDirect, Web of Science and Scopus were searched and meta-analytic data analysed using random effects models to estimate standardized mean differences. Eleven studies (2202 patients) were included. Women who achieved pregnancy had significantly lower depression scores during treatment than women who did not become pregnant (–0.302; 95% CI: –0.551 to –0.054, z = –2.387, P = 0.017; I 2 = 77.142%, P = 0.001). State anxiety scores were also lower in women who became pregnant (–0.335; 95% CI: –0.582 to –0.087, z = –2.649, P = 0.008; I 2 = 81.339%, P = 0.001). However, changes in state anxiety ( d = –0.056; 95% CI: –0.195 to 0.082, z = –0.794; I 2 = 0.00%) and depression scores ( d = –0.106; 95% CI: –0.296 to 0.085, z = –1.088; I 2 = 0.00%) from baseline to treatment were not associated with ART outcome. Clinics should aim to promote better psychosocial care to help patients manage the psychological and physical demands of ART treatment, giving realistic expectations.